DEVELOPING FOOD STORYTELLING MATERIAL OF ENGLISH FOR TOURISM - Afore Tahir Harefa; Tri Yanti Nibenia Gea; Intan Hartini Ndruru; Zun Kelvin E. A Halawa (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to develop food storytelling materials within the context of tourism in Nias, as an effort to optimize the untapped culinary potential. Using the ADDIE model, the research formulates engaging narratives to enhance tourist appeal. Trial results at the Museum Pusaka Nias indicate that 87,4% of visitors felt more inclined to try local food after interacting with the storytelling materials. The developed materials effectively educate tourists about the ingredients and cooking processes of Nias cuisine while serving as a communicative tool to convey local culture and traditions. This study recommends an increase in stakeholder awareness regarding the benefits of storytelling in promoting tourism, as well as the importance of collaboration among academics, practitioners, and the community to create authentic and sustainable culinary experiences. These findings emphasize that innovation in the presentation of culinary stories can enhance tourism marketing and preserve the cultural heritage of Nias.